Blurred lines: the timeline of supply chain resilience strategies in the grocery industry in the time of Covid-19 - Carissimi, Maria Concetta; Prataviera, Lorenzo Bruno; Creazza, Alessandro; Melacini, Marco; Dallari, Fabrizio (Springer, 2022)
To anticipate, adapt and respond to, and recover from disruptions, firms need to enhance supply chain (SC) resilience. The spread of the COVID-19 pandemic in 2020 represented a unique opportunity to investigate it empirically. This study focuses on the exploration of the resilience strategies adopted to deepen their temporal characteristics and contribute to developing the current understanding of proactivity and reactivity, something that needs to be further investigated. Multiple-case study research was conducted considering 21 Italian companies in the grocery industry. Results show that with the outbreak of the pandemic, companies adopted a set of 21 strategies that spanned five resilience categories: redundancy, flexibility, agility, collaboration, and innovation. To explain the temporal characteristics of the identified resilience strategies we propose an original taxonomy that elaborates the previous theory by introducing two new dimensions related to the strategies’ timing (“when?” and “how long?”). Each dimension can be complemented with other sub-dimensions that explain the design and activation of resilience strategies, and their utilisation and availability. The proposed taxonomy broadens the narrow view offered by existing research on the temporal dimension of resilience, as multiple layers are needed to disentangle the temporal characteristics of different strategies. It also provides an original viewpoint on interpreting the strategies’ proactivity or reactivity as their boundary is increasingly blurred. Lastly, the study opens up to future investigations of the antecedents of the design and utilisation/activation of resilience strategies, as companies could rethink their managerial decisions based on the continuous evolution of their operating environment.
Keywords: Supply chain resilience; Covid-19; Case study research; Grocery supply chains; Disruption; Strategy